Keanekaragaman serangga Ephemeroptera, Plecoptera, dan Trichoptera sebagai bioindikator kualitas perairan di Sungai Jangkok, Nusa Tenggara Barat - Ni Putu Reny Diantari; Hilman Ahyadi; Immy Suci Rohyani; I Wayan Suana (Jurnal Entomologi Indonesia, 2017)
The existence of Ephemeroptera, Plecoptera, and Trichoptera (EPT) in a body of water can be used as indicators of the quality of the waters. The aim of this study were 1) to know the diversity of EPT insects in Jangkok River, Lombok, West Nusa Tenggara, 2) determine the water quality of Jangkok River based on family biotic index (FBI), and 3) to know the effect of physical, chemical, and biological of environment parameters on the presence of EPT insects. Sampling was conducted in Jangkok River, Lombok, West Nusa Tenggara, in the dry season of July 2016. EPT groups insects were taken using water nets and eckman grab in 22 sampling points that was randomly determined in systematic random sampling. Data of physical, chemical, and biology of waters were also taken in these sampling points. Water quality is determined by the score of FBI, and the multiple correlation analysis to determine the relationship between physical and chemical parameters with the presence of EPT. Biological parameter was analyzed descriptively. The influence of biological parameter was determined by descriptive analysis. The study found 902 individuals of EPT belonging to 12 family and 12 genera. In the upstream we found 788 individuals (12 family and 12 genus), in the middlestream found 114 individuals (10 family and 10 genus), while in the downstream the EPT was absent. From the seven physical and chemical parameters of waters tested, only water temperature has significant correlation with the presence of EPT. The differences of water temperature in these area were caused by the covering and heterogeneity of the vegetation in the river side in each area. FBI score for upstream was 3.6 which indicates that the quality of the waters are very good. In the middlestream, the FBI score was 4.6, and it was categorized as good. In the downstream, results of the FBI get infinite value that entered the category as very bad.